Sex differences among subcutaneous implantable cardioverter-defibrillator recipients: a propensity-matched, multicentre, international analysis from the i-SUSI project - Schiavone, Marco; Gasperetti, Alessio; Vogler, Julia; Compagnucci, Paolo; Laredo, Mikael; Breitenstein, Alexander; Gulletta, Simone; Martinek, Martin; Kaiser, Lukas; Tundo, Fabrizio; Palmisano, Pietro; Rovaris, Giovanni; et al. (Europace, 2024)
Women have been historically underrepresented in implantable cardioverter-defibrillator (ICD) trials. No data on sex differences regarding subcutaneous ICDs (S-ICD) carriers have been described. Aim of our study was to investigate sex-related differences among unselected S-ICD recipients.Consecutive patients enrolled in the multicentre, international i-SUSI registry were analysed. Comparisons between sexes were performed using a 1:1 propensity matching adjusted analysis for age, body mass index (BMI), left ventricular function, and substrate. The primary outcome was the rate of appropriate shocks during follow-up. Inappropriate shocks and other device-related complications were deemed secondary outcomes. A total of 1698 patients were extracted from the i-SUSI registry; 399 (23.5%) were females. After propensity matching, two cohorts of 374 patients presenting similar baseline characteristics were analysed. Despite similar periprocedural characteristics and a matched BMI, women resulted at lower risk of conversion failure as per PRAETORIAN score (73.4% vs. 81.3%, P = 0.049). Over a median follow-up time of 26.5 [12.7-42.5] months, appropriate shocks were more common in the male cohort (rate/year 3.4% vs. 1.7%; log-rank P = 0.049), while no significant differences in device-related complications (rate/year: 6.3% vs. 5.8%; log-rank P = 0.595) and inappropriate shocks (rate/year: 4.3% vs. 3.1%; log-rank P = 0.375) were observed. After controlling for confounders, sex remained significantly associated with the primary outcome (aHR 1.648; CI 0.999-2.655, P = 0.048), while not resulting predictor of inappropriate shocks and device-related complications.In a propensity-matched cohort of S-ICD recipients, women are less likely to experience appropriate ICD therapy, while not showing higher risk of device-related complications.ClinicalTrials.gov Identifier: NCT0473876.
Online veröffentlicht: 2. Mai 2024
Gesehen am 09.12.2024